Nano‐hydroxyapatite‐coated PEEK implants: A pilot study in rabbit bone 1. Issue 2 (3rd August 2012) - Barkarmo, Sargon; Wennerberg, Ann; Hoffman, Maria; Kjellin, Per; Breding, Karin; Handa, Paul; Stenport, Victoria
Abstract: Osseointegration of surface‐modified polyetheretherketone (PEEK) implants was studied in vivo . A total of 18 cylinder‐shaped PEEK implants were inserted in the femurs of nine New Zealand rabbits; half were coated with nanocrystalline hydroxyapatite (nanoHA) and half were uncoated controls. Healing time was 6 weeks. Samples were retrieved with the implant and surrounding tissue, processed to cut and ground sections, and analyzed histomorphometrically. The implant surfaces were analyzed with optical interferometry, scanning electron microscopy (SEM), atomic force microscopy, and X‐ray photoelectron spectroscopy (XPS). NanoHA‐coated PEEK surfaces had lower height deviation (Sa) than controls [mean ± SD: 0.41 μm (±0.14) vs. 0.96 μm (±0.28)]. SEM images showed the nanoHA crystals as a thin layer on the polymer surface. XPS analysis of the coated implants showed a Ca/P ratio of 1.67. Histomorphometry indicated that the nanoHA‐coated implants had more bone‐to‐implant contact [16% (±4.7) vs. 13% (±9.3)] and more bone area [52% (±9.5) vs. 45% (±11.9)]. We found no difference between smooth nanoHA‐coated cylinder‐shaped PEEK implants and uncoated controls. However, higher mean bone‐to‐implant contact indicated better osseointegration in the coated implants than in the uncoated controls. The large number of lost implants was interpreted as a lack of primary stability due to implant design. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part A, 2013.